The digital consumer technology handbook a comprehensive guide to devices, standards, future directions, and programmable logic solutions - Dhir, Amit. (Amsterdam ; Boston, Mass. : Newnes, 2004)
The consumer electronics market has never been as awash with new consumer products as it has over the last couple of years. The devices that have emerged on the scene have led to major changes in the way consumers listen to music, access the Internet, communicate, watch videos, play games, take photos, operate their automobileseven live. Digital electronics has led to these leaps in product development, enabling easier exchange of media, cheaper and more reliable products, and convenient services. This handbook is a much-needed, comprehensive engineering guide to the dynamic world of today's digital consumer electronics. It provides complete details on key enabling technologies, standards, delivery and reception systems, products, appliances and networking systems. Each chapter follows a logical progression from a general overview of each device, to market dynamics, to the core technologies and components that make up that particular product. The book thoroughly covers all of the key digital consumer product categories: digital TV, digital audio, mobile communications devices, gaming consoles, DVD players, PCs and peripherals, display devices, digital imaging devices, web terminals and pads, PDAs and other handhelds, screenphones/videophones, telematics devices, eBooks and readers, and many other current and future products. To receive a FREE daily newsletter on displays and consumer electronics, go to: http://www.displaydaily.com/ Surveys crucial engineering information for every digital consumer product category, including cell phones, digital TVs, digital cameras, PDAs and many morethe only reference available to do so Has extremely broad market appeal to embedded systems professionals, including engineers, programmers, engineering managers, marketing and sales personnel1,000,000+ potential readers Helps engineers and managers make the correct design decisions based on real-world data.
Chapter 1: Generation DThe Digital Decade -- The Urge to Be Connected -- Our Daily Lives -- The Digitization of Consumer Products -- Why Digitization? -- Converging Media -- Faster and Cheaper Components -- Broadband AccessThe Fat Internet Pipe -- Home Networking -- The Day of the Digital Consumer Device -- Bringing it All Together -- -- Chapter 2: Digital Consumer Devices -- Introduction -- The Era of Digital Consumer Devices -- Market Forecast -- Market Drivers -- Phases of Market Acceptance -- Success Factors and Challenges -- Functional Requirements What About the Personal Computer? -- Digital Home -- King of AllThe Single All-Encompassing Consumer Device Summary -- Chapter 3: Digital Television and Video -- Introduction -- History of Television -- Components of a Digital TV System -- Digital TV Standards -- SDTV and HDTV Technologies -- Digital Set-top Boxes -- Market Outlook -- Integrated Digital Televisions -- Digital Home Theater Systems -- Digital Video Recorders -- Summary -- Chapter 4: Audio Players -- Introduction -- The Need for Digital AudioStrengths of the Digital Domain Principles of Digital Audio -- Digital Physical Media Formats -- Pulse Code Modulation (PCM) -- Internet Audio Formats -- Components of MP3 Portable Players -- Flash Memory -- Internet Audio Players Market Data and Trends -- Other Portable Audio Products -- Convergence of MP3 Functionality in Other Digital Consumer Devices -- Internet Radio -- Digital Audio Radio -- Online Music Distribution Summary -- Chapter 5: Cellular/Mobile Phones -- Introduction -- Definition -- LandscapeMigration to Digital and 3G -- Standards and Consortia -- Market Data -- Market Trends -- Summary -- Chapter 6: Gaming Consoles -- Definition -- Market Data and Trends -- Key Players -- Game of War -- Components of a Gaming Console -- Broadband Access and Online Gaming -- Gaming ConsolesMore Than Just Gaming Machines -- PC Gaming -- Growing Convergence of DVD Players and Gaming Consoles New Gaming Opportunities -- Summary -- Chapter 7: Digital Video/Versatile Disc (DVD) -- Introduction -- The Birth of the DVD -- DVD Format Types -- Regional Codes -- How Does the DVD Work? -- DVD Applications -- DVD Market Numbers, Drivers and Challenges -- Convergence of Multiple Services -- Summary -- Chapter 8: Desktop and Notebook Personal Computers (PCs) -- Introduction -- Definition of the Personal Computer -- Competing to be the Head of the Household -- The PC Fights Back -- Portable/Mobile Computing -- Requirements Overdose -- New PC Demand Drivers -- Summary -- Chapter 9: PC Peripherals -- Introduction -- Printers -- Scanners -- Smart Card Readers -- Keyboards -- Mice -- Summary -- Chapter 10: Digital Displays -- Introduction -- CRTsCathode Ray Tubes -- LCDLiquid Crystal Displays -- PDPPlasma Display Panels -- PALCDPlasma Addressed Liquid Crystal Display -- FEDsField Emission Displays -- DLPDigital Light Processor -- Organic LEDs -- LED Video for Outdoors -- LCoSLiquid Crystal on Silicon -- Comparison of Different Display Technologies -- FPO -- Three-dimensional (3-D) Displays -- The Touch-screen -- Digital Display Interface Standards -- Summary -- Chapter 11: Digital ImagingCameras and Camcorders -- Introduction -- Digital Still Cameras -- Digital Camcorders -- Summary -- Chapter 12: Web Terminals and Web Pads -- Introduction -- Web Pads/Tablets -- Role of the Service Provider -- Summary -- Chapter 13: Internet Smart Handheld Devices -- Introduction -- Vertical Application Devices -- Smart Handheld Phones (or Smart Phones) -- Handheld Companions -- History of the PDA -- PDA Applications -- PDA Form Factors -- Components of a PDA -- Summary -- Chapter 14: Screen and Video Phones -- Introduction -- Definition -- History -- Screenphone Applications -- The Screenphone Market -- Categories and Types -- The Public Switched Telephone Network (PSTN) vs. the -- Internet Protocol (IP) Network -- Screenphone Components -- Video Phone (Webcam) Using the PC -- e-Learning -- Summary -- Chapter 15: Automotive Entertainment Devices -- Introduction -- The Evolving Automobile -- What is Telematics? -- The Automotive Electronics Market -- The Controversy -- The Human Touch -- Pushbutton Controls Versus Voice Recognition -- Standardization of Electronics in Automobiles -- Standards for In-vehicle Power Train and Body Electronics -- Standards for In-vehicle Multimedia Electronics -- Components of a Telematics System -- Manufacturers and Products -- Satellite Radio -- The Vision for Telematics -- Summary -- Chapter 16: eBooks -- Introduction -- What is an eBook? -- Benefits of Using eBooks -- Reading eBooks -- Market -- Copy Protection -- Technology Basics -- Manufacturers and Products -- Challenges -- Summary -- Chapter 17: Other Emerging and Traditional Consumer Electronic Devices -- Introduction -- NetTV -- E-mail Terminals -- Wireless E-mail Devices -- Pagers -- Internet-Enabled Digital Picture Frames -- Pen Computing or Digital Notepad -- Robot AnimalsRobot Dogs -- White Goods -- Lighting Control -- Home Control -- Home Security -- Energy Management Systems -- Home Theater and Entertainment Systems -- Magnetic Recording -- VCRsVideo Cassette Recorders -- Custom-Installed Audio Systems -- Receivers/Amplifiers -- Contents -- Home Speakers -- Vehicle Security -- Vehicle Radar Detectors -- Summary -- Chapter 18: The Digital Dream Home -- Emergence of Digital Homes -- The Digital Home Framework -- Productivity Increases in the Connected World -- Broadband Access -- Home Networking -- The Different Needs of Different Consumer Devices -- Residential Gateways -- Middleware -- Digital Home Working Group -- SummaryThe Home Sweet Digital Home -- Chapter 19: Programmable Logic Solutions -- Enabling Digital Consumer Technology -- What Is Programmable Logic? -- SiliconProgrammable Logic Devices (PLDs) -- IP Cores, Software and Services -- Xilinx Solutions for Digital Consumer Systems -- Addressing the Challenges in System Design -- Using FPCs in Digital Consumer Applications -- Memories and Memory Controllers/Interfaces -- Discrete Logic to CPLD: The Evolution Continues -- Signaling -- Xilinx Solutions for EMI Reduction in Consumer Devices -- Summary -- Chapter 20: Conclusions and Summary -- Landscape -- The Ultimate Digital Consumer Device -- Room for Many -- Components of a Typical Digital Consumer Device -- The Coming of the Digital Home -- Key Technologies to Watch -- In Closing -- Index.
Includes index.
Keywords: Digital electronics -- Handbooks, manuals, etc; Household electronics -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc